Balance of Payments Compilation Guide. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
A companion document to the fifth edition of the Balance of Payments Manual, the Balance of Payments Compilation Guide shows how the conceptual framework described in the Manual may be implemented in practice. The primary purpose of the Guide is to provide practical guidance for using sources and methods to compile statistics on the balance of payments and the international investment position. The Guide is designed to assist experienced and aspiring balance of payments compilers and statisticians in understanding the relative strengths and weaknesses of various approaches. The material reflects the emergence of new data sources and adaptations in the application of statistical methodologies to changing circumstances. Discussed in the Guide are all of the tasks that a BOP compiler normally performs. Appendices contain a set of model BOP questionaires and a set of model BOP publication tables. Relationships between the balance of payments statistics and relevant aspects of national accounts are covered as well.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet